UNIVERSITY NETS IN COLOMBIA NEW HISTORICAL BACKGROUND FOR THE UNIVERSITY - Soto Arango, Diana Elvira (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
The university net belongs to the evolution and building academic in the University degree at the end of the twentieth century. In Colombia they are new; their aim is to offer a set of academic high level programs as Masters and Doctorates studies. In this work it will do a historical level balance starting in a first term, the decreto 080 of 1980 in the constitution. The second term, from the Law 30 of 1992 had the impact in the same Nets constructions. Thus, the education doctorates are created with the style of organization of academic nets. In this case RUDECOLOMBIA, since the first construction of the Net’s is identity focus on objectives of regional education development ad with projects of nation construction.